Oriented growth of nanocrystalline gamma ferric oxide in electrophoretically deposited films - Bhave, T. M.; Balasubramanian, C.; Nagar, H.; Kulkarni, S.; Pasricha, R.; Bakare, P. P.; Date, Sadgopal K.; Bhoraskar, S. V. (Hyperfine Interactions, 2005)
Films of nanocrystalline gamma-Fe2O3 were deposited on silicon substrates by using the technique of electrophoretic deposition. The precursor powder was nanocrystalline gamma-Fe2O3, which was synthesized, using DC arc plasma in the oxygen ambient by vapour-vapour interaction in gas phase condensation; at a stabilized arc current of 40 A. This powder was characterized by X-ray diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and Mossbauer Spectroscopy. An increase in directional coercivity was observed in case of films deposited on silicon substrates, which is dramatically significant. Preferred orientation of almost similar sized nanocrystalline magnetic domains in deposited films is evident from the results of X-ray diffraction and Transmission Electron Microscopy results. The preferred alignment of the nanocrystallites seems to be responsible for the significant changes observed in magnetic properties of films.

Thermal, magnetic and spectral studies of metal-quinone complexes Part III. radical coordination and hydrogen bonding mediated exchange interaction in copper-hydroxyquinone complex - Salunke-Gawali, S.; Rane, S. Y.; Boukheddaden, K.; Codjovi, E.; Linares, J.; Varret, F.; Bakare, P. P. (Journal of Thermal Analysis and Calorimetry, 2005)
The reaction of CuCl with 2HNQ, ( viz. 2- hydroxy- 1,4- naphthoquinone), in methanol results in [Cu-2( II, II)(4HNSQ)(2)(ONQ)(2)(H2O)(4)], Cu- 3 complex; [ where ONQ is the deprotonated oxidized form of ligand ( viz. 2- oxido- 1,4- naphthoquinone) and 4HNSQ one electron reduced tautomeric form of the ligand (i.e. 4- hydroxy - 1,2- naphthosemiquinone)]. The mixed valent redox ligation is confirmed in [ 9] by us. In present report complex Cu- 3 investigated by variable temperature magnetic susceptibility measurements ( SQUID), X and Q- band EPR, DSC and CV techniques. A break is observed in the chi(m)(-1) vs. T plot similar to 200 K in Cu- 3 which is attributed to a phase transition. In Cu- 3 a quintet state ( S= 2) is populated above 200 K by the molecular association of two exo Cu( II)( 4HNSQ) units via hydrogen bonding between Cu(ONQ) unit of endo ligands in dimer. Magnetic susceptibility data is treated with tetramer model with S= 1/2,1/2,1/2,1/2. The interdimer triplet- triplet interaction ( J) in two [ Cu( 4HNSQ)] units and intradimer ( zJ(1)) interaction between [ Cu( II)( 4HNSQ)] are best fitted with J= -50 cm(-1) and zJ(1)= 28 cm(-1), respectively, using g= 2.2. `Quintet- triplet' phase transition occurs with an enthalpy change of 31.83 kJ mol(-1) estimated from DSC. Cu( II)double left right arrow Cu( I) and NSQ double left right arrow CAT redox couples at E-1/2= 0.68 V and E-1/2 = -1.12 V, respectively are result of exo ligands and Cu( II) ions interaction, while shifts of ligand based peaks viz. NQ -> NSQ and NSQ double left right arrow CAT at - 0.44 and - 0.67 V towards positive potential on complexation are due to electron transfer interactions between endo ligand and Cu( II) ion.
Keywords: antiferromagnetic coupling; copper complexes; Lawsone; model complexes; quinones; triplet state

Magnetic properties of NiCuZn ferrites synthesized by oxalate precursor method - Ghodake, S. A.; Ghodake, U. R.; Sawant, S. R.; Suryavanshi, S. S.; Bakare, P. P. (Journal of Magnetism and Magnetic Materials, 2006)
Ni-Cu-Zn ferrites have been synthesized by employing co-precipitation technique using oxalate precursors. X-ray diffractograms did not show impurity phases, indicating single-phase formation of the ferrites. The diffractograms of oxalate complex decomposed at 650 degrees C show that ferritization is complete up to 650 degrees C. Lattice parameter a (angstrom) was found to decrease with the addition of Ni2+ which is attributed to ionic sizes of Ni2+ (0.69 angstrom), which replaces Cu2+ (0.72 angstrom). From the thermogravimetric studies it is observed that the experimentally observed total mass loss (%), agrees with theoretically calculated mass loss (%) indicating maintenance of requisite stoichiometry. Initial permeability (mu(i)) shows increase when Ni2+ is added up to x = 0.15 while for (x > 0. 15), it decreases. The increase in initial permeability (mu(i)) is attributed to monotonic increase in Ms, and K-1 on addition of Ni2+. However, the microstructure and density (porosity) also influence mu(i) variations. The decrease in pi is attributable to increase of K-1. The composition with density 91.14% exhibits large mu(i) which also tends to increase with temperature up to 60 degrees C. Thus its usable range extends up to 60 degrees C. This samples has T-c near to 160 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: initial permeability; magneticproperties; Magnetization; NiCuZn ferrites; XRD

Preparation of gamma-Fe2O3 nanoparticles using DC thermal arc-plasma route, their characterization and magnetic properties - Banerjee, Indrani; Khollam, Y. B.; Balasubramanian, C.; Pasricha, R.; Bakare, P. P.; Patil, K. R.; Das, A. K.; Bhoraskar, S. V. (Scripta Materialia, 2006)
gamma-Fe2O3 particles were prepared, for the first time, using a direct current thermal arc-plasma route. The powder was characterized using X-ray diffraction, Mossbauer spectroscopy, X-ray photoelectron spectroscopy, chemical analysis, vibrating sample magnetometry C and transmission electron microscopy. The high purity, stoichiometry and spherical morphology of the gamma-Fe2O3 particles (saturation magnetization = 79 emu g(-1) and coercivity = 348 Oe) were confirmed. (c) 2006 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: chemical analysis; DC thermal arc-plasma route; maghemite; Mossbauer spectroscopy; XPS

Role of ligands in the formation, phase stabilization, structural and magnetic properties of alpha-Fe2O3 nanoparticles - Joshi, Satyawati S.; Patil, Prajakta R.; Nimase, Madhav S.; Bakare, P. P. (Journal of Nanoparticle Research, 2006)
The electrochemical synthesis of alpha Fe2O3 nanoparticles was performed using quaternary ammonium salts viz. TPAB, TBAB and TOAB in an organic medium by optimizing current density and molar concentration of the ligand. The role of ligands in the formation of alpha phase, structure and magnetic properties was investigated in details. The effect of increasing chain length on the particle size confirmed that as the chain length increases from propyl to octyl, the particle size decreases. X-ray diffraction spectra of as prepared samples and TEM analysis confirmed the amorphous nature of iron oxide. TEM showed beads of iron oxide joined together with a size distribution in the range of 6-30 nm. The Mossbauer studies also support this observation that for the lowest particle size, the line width is broader which successively reduces with increase in particle size. Iron oxide capped with TOAB indicated superparamagnetic nature at room temperature. The resultant internal magnetic field of 506 mm/s due to hyperfine splitting clearly established the formation of alpha-Fe2O3 The infrared spectroscopy and pH measurements revealed the binding of tetra alkyl ligand with iron oxide. The IR spectra and the increase in basicity of as prepared samples confirmed the formation of hydrated iron oxide. Above 800 degrees C the spectra indicated only iron oxide. Surface area obtained by BET method was 205 m(2)/g.
Keywords: Alkyl chain length; alpha-Fe2O3; Electrochemistry; magnetic properties; Nanoparticles; narrow size distribution